Effect of supplementation with probiotics or synbiotics on cardiovascular risk factors in patients with metabolic syndrome: a systematic review and meta-analysis of randomized clinical trials - Chen, TingRui; Wang, Jing; Liu, ZeKun (Frontiers in Endocrinology, 2024)
Abstract: Purpose: The effectiveness of probiotics or synbiotics in adults with metabolic syndromes (MetS) remains controversial, this meta-analysis will further analyze the effects of probiotics or synbiotics on cardiovascular factors in adults with MetS. Methods: We searched Web of Science, PubMed, Embase, Cochrane Library and other databases for randomized controlled trials (RCTs) on the effects of probiotics or synbiotics on MetS in adults up to July 2023, and used RevMan 5.4.0 software for statistical analysis. Results: This analysis included eleven RCTs (n = 608 participants), and the results showed that compared with the control group, supplementation with probiotics or synbiotics reduced body mass index (weighted mean difference, WMD = -0.83, 95% CI = [-1.21, -0.44], P <0.0001, n = 9), low-density lipoprotein (LDL-c) (standard mean difference, SMD = -0.24, 95% CI = [-0.41, -0.08], P = 0.004, n = 10), fasting blood glucose (FBG)(SMD = -0.17, 95% CI = [-0.33, -0.01], P = 0.03, n = 11), but had no beneficial effect on systolic blood pressure (SBP) (WMD = 1.24, 95% CI = [-2.06, 4.54], P = 0.46, n = 8) in MetS patients. Conclusions: Supplementation with probiotics or synbiotics can reduce BMI, LDL-c, FBG in patients with MetS, but our findings did not demonstrate a favourable effect on reducing SBP. Future studies with larger samples and longer intervention periods are needed.